THE EFFECT OF PROFITABILITY AND INTANGIBLE ASSETS ON TRANSFER PRICING BEHAVIOR (EMPIRICAL STUDY OF COAL MINING SUB-SECTOR COMPANIES LISTED ON THE IDX IN 2018-2022) - Yesa Amanda Putri; Ina Iskandar; Agustine Dwianika (RELEVAN : Jurnal Riset Akuntansi, 2023)
This study aims to provide empirical evidence regarding the effect of profitability and intangible assets on transfer pricing behavior in coal mining sub-sector companies in Indonesia. The population in this study includes coal mining sub-sector companies listed on the IDX from 2018 to 2022. Determination of the sample using the purposive sampling method with the final total sample being 18 companies. The research method used is descriptive quantitative and the data analysis method is multiple regression analysis with panel data. The results showed that profitability has a negative effect on transfer pricing behavior. Companies with high profitability tend not to practice transfer pricing. Other results show that the value of intangible assets has no effect on transfer pricing behavior.